Factors Influencing Community Decisions in Choosing Community Health Centers for Promotive and Preventive Health Services: Literature Review - Lailatul Hasanah; Nurul Fitriyah; Rosalia Nindy Prastika Sari; Diansanto Prayoga (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Minister of Health Regulation Number 43 of 2019 stated that Community Health Centers (Puskesmas) were health service facilities that provided community health efforts (UKM) and individual health efforts (UKP) at the first level, prioritizing promotive and preventive efforts in their working areas. The reason for composing this article was crucial, as Community Health Centers, as both general health services and providers of promotive and preventive services, were expected to attract public interest.. Objective: Analyzed factors influencing community choices of health centers for promotive and preventive services. Method: A qualitative research study was conducted, employing a literature review via electronic databases, particularly utilizing Scopus journal sources. Keywords like